Sistem Informasi Geografis Pemetaan Sebaran Data Covid-19 Pada Puskesmas Kerongkong Kabupaten Lombok Timur Berbasis Web - Imam Fathurrahman; Moh Farid Wajdi; Hadian Mandala Putra; Baiq Vinaru Widarina (Infotek: Jurnal Informatika dan Teknologi, 2022)
An information system is a collection of data or facts that are processed and processed in such a way as to produce something that can be understood and can be useful for the recipient. Among the general public, the need for accurate and fast information is urgently needed at this time, especially information regarding the spread of the Covid-19 disease that is hitting the world today. Covid-19 (Coronavirus) is a virus that can attack the respiratory tract and can be transmitted to anyone through droplets of phlegm. However, in conveying information by the Kerongkong Health Center officers regarding the Covid-19 distribution area in the Suralaga sub-district, they still use the socialization method. This method is considered right on target, but it is considered less effective for villages that have a fairly high distribution rate in the Suralaga sub-district. Therefore, an information system for Mapping the Covid-19 Spread Area is needed that is fast and accurate in conveying information to the public, the goal is to make it easier for the puskesmas to take preventive actions against areas that have a fairly high spread rate by looking at the location of the distribution area in the sub-district. suralaga. WebGIS is a web-based geographic information system consisting of several components, namely mapping graphic design, digital maps with geographic analysis, computer programs, and a database that are interconnected into one part. In the preparation of the stages of this research carried out by means of data collection, system design, system creation stage, testing and evaluation. The existence of WebGIS mapping the patient's location can help the throat health center in collecting data on Covid-19 patients and can quickly provide information to the public.